L’ekphrasis photographique dans Dora Bruder de Patrick Modiano : entre magnétisme et réfraction - Valeria Sperti (Cahiers de Narratologie)
The article analyses – starting from the first edition of Patrick Modiano's Dora Bruder – the representation of the photographic act, the nine ekphrasis of portraits of the Bruder's family and their daughter and the two puzzling pictures of a social and urban world which disappeared. The goal of the analysis is to show the impotence of the photographic object when faced with the reconstruction of Dora's story and to compare it to the official documents inserted in the diegesis. The analysis then considers the pictures in prose to show how writing magnetises and refracts the cliché, being this document absent in the narration. The textual coherence of these descriptions on the level of the discourse and of the significance conceals some gaps. The absence of emotional connotation – reserved to the ekphrasis of family portraits – appears like a gap necessary for the narrator to create a resonance, through narrative, with the disappeared girl.